Hidrólisis enzimática de chenopodium quinoa willd “quinua”, determinando sus parámetros cinéticos: ph, temperatura y concentración de sustrato. - Terry Calderón, Víctor Manuel (2014)
The process of hydrolysis was carried out on a suspension of quinoa flour in water in a proportion of 1 in10 parts of water, previously gelatinized, to which was added an equivalent suspension of enzymes of 1,5 g/1000 g (50% of alpha amylase and 50% protease). With that, proteins were solubilized and starch was reduced to reducing su- gars, obtaining a liquid product at an average concentration of 8,5% that was later con- centrated to 45% of total solids. The hydrolysis process allows, on the basis of 1 kg of quinoa flour, toobtain80 to 85% of hydrolyzed material from20 to 15% of cellulosic residue, proteins and carbohydrates, non-digestible by the enzymes. The experiences that were carried out brought as results the following optimum values of kinetic parameters: Concentration of substrate: 10,0 %; Temperature: 60 ºC; pH: 5,0 and enzyme con- centration: 1,5 g/ 1000 g. The system allows on the basis of 1 kg, the following values: percentage of hydrolyzed proteins: 74,00%; percentage of reducing sugars: 94,00%